The Routledge handbook of the influence of built environments on diverse childhoods - Bishop, Kate (Lecturer on the built environment); Dimoulias, Katina (New York, NY : Routledge, 2024)
"Children and young people are often discussed as if they are homogenous groups. The reality is of course very different with an enormous variation within each of these groups and in any domain of experience pertaining to childhood or adolescence. Driven by personal, socio-cultural, geographic, or economic circumstances, many children and young people worldwide are experiencing a totally different reality to those who fit with more mainstream patterns of childhood. This has substantial implications for their socio-physical environmental experience and our understanding of their physical environmental needs. The aim of this book is to draw attention to these alternate realities for a number of these groups of children and young people, highlighting the unique and different considerations associated with their particular circumstances in each instance and to identify the repercussions for their physical environmental needs. Ultimately we create an evidence-based discussion which can be used by designers, planners and policy makers, and those delivering services and programs to children and young people, as a basis to make informed decisions on how to work with the groups of children and young people in our book, for better environmental provision"--
Keywords: Children -- Social conditions -- Cross-cultural studies; Youth -- Social conditions -- Cross-cultural studies; Equality -- Social conditions; Distributive justice; Built environment; Marginality, Social; Land use -- Planning; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development